ANALISIS PELAKSANAAN SERTIFIKAT LAIK FUNGSI PADA PERUMAHAN SUBSIDI DI PROVINSI NUSA TENGGARA TIMUR - Lamdu, Anita Kurniati Alachmad; Koreh, Andreas Welem; Fernandez, Reyneldis Laurensia (Jurnal Al Ulum LPPM Universitas Al Washliyah Medan, 2024)
Problems with the implementation of subsidised housing construction such as the dimensions/size of the concrete sloof installed are not in accordance with the standards to the availability of drinking water, electricity and utilities in housing built by developers, there are even findings of houses that have not been electrified To anticipate that events like the above do not recur, the developer is obliged to complete the SLF document (Certificate of Good Function) This research was conducted to analyse the implementation of a certificate of good function on subsidised houses in Kupang City The method of analysis used in this study includes the statistical method of computer programming descriptions, on Microsoft Office Excel. The results of the analysis show that the readiness and concern of subsidised housing developers in Kupang City towards the Certificate of Functioning (SLF) of subsidised house buildings is included in the unprepared category with the results of a comparison of 27% of developers who have taken care of the SLF and 73% of developers have not arranged the SLF. In addition, the analysis shows that there are no major obstacles faced by developers in the application of the Certificate of Functioning (SLF). This can be seen from the developer's understanding of the methods and tools of building inspection that are in accordance with the criteria for reliable buildings according to the SLF checklist according to the PUPR Ministerial Regulation No.27/PRT/M/2018